Sucrose transport into barley seeds: Molecular characterization of two transporters and implications for seed development and starch accumulation - Sauer, Norbert; et al. (Plant Journal, 2000)
In order to understand sucrose transport in developing seeds of cereals at the molecular level, we cloned from a caryopses library two cDNAs encoding sucrose transporters, designated HvSUT1 and HvSUT2. Sucrose uptake activity was confirmed by heterologous expression in yeast. Both transporter genes are expressed in maternal as well as filial tissues. In a series of in situ hybridizations we analysed the cell type-specific expression in developing seeds. HvSUT1 is preferentially expressed in caryopses in the cells of the nucellar projection and the endospermal transfer layer, which represent the sites of sucrose exchange between the maternal and the filial generation and are characterized by transfer cell formation. HvSUT2 is expressed in all sink and source tissues analysed and may have a general housekeeping role. The rapid induction of HvSUT1 gene expression in caryopses at approximately 5-6 days after fertilization coincides with increasing levels of sucrose as well as sucrose synthase mRNA and activity, and occurs immediately before the onset of rapid starch accumulation within the endosperm. Starch biosynthesis requires sucrose to be imported into the endosperm, as direct precursor for starch synthesis and to promote storage-associated processes. We discuss the possible role of HvSUT1 as a control element for the endospermal sucrose concentration.